COMMUNITY EMPOWERMENT MODEL THROUGH OPTIMIZATION OF THE ROLE OF INDONESIAN MIGRANT WORKERS (PMI) PURNA IN ENCOURAGING ACHIEVEMENT OF THE SUSTAINABLE DEVELOPMENT GOAL IN EAST LAMPUNG REGENCY: COMMUNITY EMPOWERMENT MODEL THROUGH OPTIMIZATION OF THE ROLE OF INDONESIAN MIGRANT WORKERS (PMI) PURNA IN ENCOURAGING ACHIEVEMENT OF THE SUSTAINABLE DEVELOPMENT GOAL IN EAST LAMPUNG REGENCY (Administratio, 2019)
Indonesian Migrant Workers (PMI) who have ended their employment contracts, are called purna PMI. Full PMI who have returned from working abroad bring enormous remittances. Remittances that are not managed properly will run out for consumptive purposes, so that it can cause purna PMI who have returned from working abroad to depart again as PMI. Therefore, purna PMI needs to be fostered and empowered with the aim of having sustainable income, thus having the opportunity to be able to create jobs for the surrounding communities This research uses descriptive research with a qualitative approach. Based on the results of the study, there is currently a purna PMI empowerment program, namely the Program (1) Productive Migrant Village by the Ministry of Manpower, (2) Empowerment program for PMI Gold by the National Agency for Placement and Protection of Indonesian Workers (BNP2TKI). This program is actually relatively good, but the program in East Lampung Regency has not run optimally. This is because there are still obstacles such as human PMI resources that are still lack of knowledge, difficult access to capital, marketing of entrepreneurial products that have not been maximized and lack of local partners who are involved in the empowerment process. This has led to the need for synergies in creating and implementing an empowerment model, which can be a reference model for empowerment of regions with full PMI follicle to encourage the achievement of sustainable development in East Lampung Regency. Keywords : PMI purna, Remittance and Empowerment